Development of the Evaluation System of Islamic Education in Indonesian Pondok Pesantren - Nailil Maghfiroh; Saadi; Mukh Nursikkin (Sekolah Tinggi Ilmu Tarbiyah Madani Yogyakarta, 2023)
This research aims to explore the concept of evaluation in the Quran, innovations in developing evaluation for Islamic education (PAI) in traditional and